On Plato's Republic II, 376d9 - III, 403c8 - Luís Felipe Bellintani Ribeiro (Universidade Federal de Santa Catarina, 2017)
The section II 376d9 - III 403c8 of the Plato's Republic, in which Socrates and his interlocutors discuss about the mousiké, can be clearly demarcated and isolated, and from there can be extracted enough material to form a "platonic aesthetics" in a normative sense. On the other hand, the content of this "treatise on music" is so attached to the rest of the work that its reading may instead provide a consideration of the whole of the platonic project, beyond the boundaries of the treatise, and the role played in this project by the sensation, the beauty and the art.